Pottery step-by-step. (New York : Collier Books, 1976)
Introduces various techniques of pottery-making, and tells how to decorate and glaze ceramic items and how to prepare, pack and fine most types of electric kilns.
Introduction to Pottery -- Clay Preparation -- Pinch Pots -- Coiled Pots -- Slab Pots -- Moulded Dishes and Pots -- Slip Cast Forms -- Carved Forms -- Thrown Bowl -- Trimming Thrown Forms -- Composite Thrown Forms -- Hanging Planter -- Jug and Teapot -- Oxides -- Surface Decoration -- Slip Decoration -- Inlaid Decoration -- The Damp Cupboard and Drying -- Packing and Firing the Kiln -- Glazes and Glost firing -- The Sadust Kiln -- Enamels and Beads -- Storage and Reconstitution of Clay -- List of Suppliers -- Some Further Reading.
"A Studio Vista book."
Keywords: POTTERY